Hippocampal glial inflammatory markers are differentially altered in a novel mouse model of perimenopausal cerebral amyloid angiopathy - Platholi, Jimcy; Marongiu, Roberta; Park, Laibaik; Yu, Fangmin; Sommer, Garrett; Weinberger, Rena; Tower, William; Milner, Teresa A.; Glass, Michael J. (Frontiers in Aging Neuroscience, 2023)
Dementia is often characterized by age-dependent cerebrovascular pathology, neuroinflammation, and cognitive deficits with notable sex differences in risk, disease onset, progression and severity. Women bear a disproportionate burden of dementia, and the onset of menopause (i.e., perimenopause) may be a critical period conferring increased susceptibility. However, the contribution of early ovarian decline to the neuroinflammatory processes associated with cerebrovascular dementia risks, particularly at the initial stages of pathology that may be more amenable to proactive intervention, is unknown. To better understand the influence of early ovarian failure on dementia-associated neuroinflammation we developed a model of perimenopausal cerebral amyloid angiopathy (CAA), an important contributor to dementia. For this, accelerated ovarian failure (AOF) was induced by 4-vinylcyclohexene diepoxide (VCD) treatment to isolate early-stage ovarian failure comparable to human perimenopause (termed “peri-AOF”) in transgenic SWDI mice expressing human vasculotropic mutant amyloid beta (Aβ) precursor protein, that were also tested at an early stage of amyloidosis. We found that peri-AOF SWDI mice showed increased astrocyte activation accompanied by elevated Aβ in select regions of the hippocampus, a brain system involved in learning and memory that is severely impacted during dementia. However, although SWDI mice showed signs of increased hippocampal microglial activation and impaired cognitive function, this was not further affected by peri-AOF. In sum, these results suggest that elevated dysfunction of key elements of the neurovascular unit in select hippocampal regions characterizes the brain pathology of mice at early stages of both CAA and AOF. However, neurovascular unit pathology may not yet have passed a threshold that leads to further behavioral compromise at these early periods of cerebral amyloidosis and ovarian failure. These results are consistent with the hypothesis that the hormonal dysregulation associated with perimenopause onset represents a stage of emerging vulnerability to dementia-associated neuropathology, thus providing a selective window of opportunity for therapeutic intervention prior to the development of advanced pathology that has proven difficult to repair or reverse.